Genome-Wide Mapping of Loci Explaining Variance in Scrotal Circumference in Nellore Cattle - Utsunomiya, Yuri T. [UNESP]; Carmo, Adriana S. [UNESP]; Neves, Haroldo H. R. [UNESP]; Carvalheiro, Roberto [UNESP]; Matos, Marcia C. [UNESP]; Zavarez, Ludmilla B. [UNESP]; Ito, Pier K. R. K. [UNESP]; O'Brien, Ana M. Perez; Soelkner, Johann; Porto-Neto, Laercio R.; Schenkel, Flavio S.; McEwan, John; et al. (Public Library Science, 2014)
The reproductive performance of bulls has a high impact on the beef cattle industry. Scrotal circumference (SC) is the most recorded reproductive trait in beef herds, and is used as a major selection criterion to improve precocity and fertility. The characterization of genomic regions affecting SC can contribute to the identification of diagnostic markers for reproductive performance and uncover molecular mechanisms underlying complex aspects of bovine reproductive biology. In this paper, we report a genome-wide scan for chromosome segments explaining differences in SC, using data of 861 Nellore bulls (Bos indicus) genotyped for over 777,000 single nucleotide polymorphisms. Loci that excel from the genome background were identified on chromosomes 4, 6, 7, 10, 14, 18 and 21. The majority of these regions were previously found to be associated with reproductive and body size traits in cattle. The signal on chromosome 14 replicates the pleiotropic quantitative trait locus encompassing PLAG1 that affects male fertility in cattle and stature in several species. Based on intensive literature mining, SP4, MAGEL2, SH3RF2, PDE5A and SNAI2 are proposed as novel candidate genes for SC, as they affect growth and testicular size in other animal models. These findings contribute to linking reproductive phenotypes to gene functions, and may offer new insights on the molecular biology of male fertility.